The Effect of Family-Centered Empowerment Model (FCEM) on Improving Family Functioning of Children Diagnosed with Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency - Izadpanah A; Sheikhi F; Pourblouch O; Bameri F; Kalkali S (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction and Aim: Caring for child with glucose-6-phosphate dehydrogenase (G6PD) deficiencycauses a lot of stress for parents. Family-centered empowerment model is one of the educational programs.Materials and Methods: A controlled clinical trial was conducted on parents of children with G6PDdeficiency that was referred to Iran Hospital of Iranshahr. The participants were randomly divided intoan experimental group (n = 30) and a control group (n = 30). To collect the data, the Family AssessmentDevice (FAD) was completed by the children’s parents before and after the intervention. The FAD scalesdemonstrated fairly good internal consistency (the Cronbach’s alpha of the questionnaire ranged from 0.72to 0.92 and its validity and reliability were 0.76 to 0.66 indicating the acceptable values. The family-centeredempowerment model was implemented during four sessions. One month after the intervention, the subjectscompleted the questionnaire again and finally the data were analyzed by the statistical tests.Results: Both the paired and independent sample t-tests were used for all statistical analyses at a significancelevel of P>0.05. Also, both the chi-square test and the Fisher’s exact test were used to compare qualitativevariables in two groups. The mean FAD scores of the intervention group were significantly decreased from152/4 to 1.120 (P<0.001), while no statistically significant difference was observed in the mean FAD scoresfor controls before and after the intervention. Furthermore, the mean FAD scores in the intervention groupwere decreased to 32.3 units and up to 0.6 unit in the controls, and the difference between two groups wasstatistically significant (P<0.001).Conclusion: According to the results obtained, the implementation of family-centered empowerment modelhas a significant effect on improving the family functioning of children diagnosed with G6PD deficiency.Therefore, it is recommended to implement in health centers in order to prevent recurrent attacks of thisdisease.